Preparation method of aluminum-silicon-copper strip

By using metal powder to prepare cylindrical core rods and fused with silicon bronze alloy clad tubes, the existing aluminum-silicon copper strip preparation methods and difficult component control problems are solved, and the preparation of high-performance aluminum-silicon copper strips is realized, which is suitable for a wider range of applications.

CN119876658APending Publication Date: 2025-04-25SHENZHEN XINGUANYA TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411635788.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing aluminum-silicon copper strip preparation methods are complicated and expensive, resulting in high production costs and difficult to control the content and mixing uniformity of each metal component, affecting the surface and mechanical properties of the product.

Method used

The cylindrical core rod is made by smelting and annealing, and the core rod is inserted into the silicon bronze alloy clad tube, and is fully fused with melting and ultrasonic assistance. Finally, the aluminum-silicon copper strip is produced by extrusion, rolling, annealing, drawing and slitting.

Benefits of technology

It improves the component accuracy, product surface performance and mechanical properties of aluminum-silicon copper strips, enhances its flexibility, extension, toughness, wear resistance, corrosion resistance and tensile strength, and is suitable for harsh environments and expands its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876658A_ABST
    Figure CN119876658A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal material processing, in particular to a preparation method of an aluminum-silicon-copper strip, which comprises the following steps: S1, mixing 35-50 parts by mass of aluminum-silicon alloy powder, 10-20 parts by mass of aluminum-copper alloy powder and 30-55 parts by mass of aluminum powder to obtain mixed powder; s2, preparing a precursor alloy material; s3, preparing a second-phase particle dispersion liquid; s4, preparing a modified precursor alloy material; s5, processing the modified precursor alloy material into a cylindrical core rod; s6, preparing a preform rod; s7, horizontally moving the prefabricated rod into a smelting furnace to enable the prefabricated rod to be in a molten state, and preparing a strip fusion solution under the assistance of ultrasonic waves; and S8, the strip fusion liquid prepared in the step S7 is extruded, rolled and annealed, and then the aluminum-silicon-copper strip is prepared after drawing and slitting. The flexibility and ductility of the aluminum-silicon-copper strip are improved, the aluminum-silicon-copper strip has the high surface performance of toughness, wear resistance and high tensile strength, the application range of the aluminum-silicon-copper strip is greatly widened, and the aluminum-silicon-copper strip has wide market prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal material processing, in particular to a method for preparing an aluminum-silicon-copper strip. Background Art

[0002] Strip is a strip metal material with a large length-width ratio and supplied in rolls. It is widely used, especially in emerging electronic manufacturing, automobile manufacturing, and new energy fields such as solar energy and wind energy. With the development of production technology and the improvement of people's requirements for strip structure and performance, single metal materials are gradually unable to meet people's needs. Therefore, new composite metal materials have emerged, because composite metal materials generally have many advantages of multiple metals, such as light weight, high strength, and corrosion resistance. Metal copper has good electrical conductivity and welding performance, but it is expensive and difficult to process; metal aluminum has the advantages of good electrical conductivity and relatively low price, but its welding performance, wear resistance, and arc extinguishing performance are poor; silicon has the advantages of good thermal stability, high hardness and low price, but it is easy to leak electricity and produce impurity sound at high temperature, which limits its application. It is precisely because of the unique advantages and disadvantages of copper, aluminum, and silicon that they have attracted the attention of a large number of scholars. They have composited multiple materials into strips to overcome the limitations of single metal applications.

[0003] The preparation of strips generally adopts hot rolling. For example, in the prior art, patent number CN104669705B "A copper / aluminum composite strip and its preparation method" discloses that the original metal strips copper strip, aluminum-silicon alloy strip, and aluminum strip are first annealed, and then the annealed strips are sequentially passed through an uncoiler, a straightener, a grinding device, a photoelectric alignment, and a composite rolling mill to complete the first composite rolling, and finally 8 passes of fine rolling are performed to obtain the copper / aluminum composite strip. It can be seen that the process steps adopted in this patent are cumbersome, the equipment is complex and expensive, which increases the preparation cost, and this patent uses metal strips as raw materials, and the content of each metal component is not easy to control and difficult to mix evenly, all of which put higher requirements on the preparation method and operation process. For another example, the patent number CN103464935B, “A method for preparing an aluminum-silicon-copper solder”, improves the mixing method of the various metal components in the composite material, and specifically discloses determining the ratio of aluminum-silicon wire and copper-silicon wire according to the required aluminum-silicon-copper solder composition requirements, and making thin wires from silicon-aluminum alloy and copper-silicon alloy produced by conventional methods, and then mixing the silicon-aluminum wire and copper-silicon wire into round or flat-belt solder ropes, and then drawing / rolling them into the required finished solder fineness requirements, and finally laser scanning, sintering and fusing them in sections to form a uniform aluminum-silicon-copper fine solder product. It can be seen that this patent produces a uniform aluminum-silicon-copper fine solder product, but this patent is a silicon-aluminum alloy doped with copper-silicon alloy, and its performance has been improved to a certain extent, but its surface toughness, wear resistance, corrosion resistance and tensile strength still need to be further improved. To this end, people have improved the flexible aluminum-silicon alloy by wrapping a mixed powder composed of brittle material aluminum-silicon-copper powder and aluminum brazing powder on its outer skin to make a brittle aluminum-silicon-copper brazing filler metal (such as patent CN111299897A) to enhance the surface performance. Specifically, the method is to add the mixed powder through a powder feeder during the welding wire forming process, thereby winding up a flexible tubular flux-cored welding wire, and then drawing to obtain a finished product. The surface brittleness is enhanced, but it is easy to cause unevenness on the product surface, or waste of powder during the powder adding process.

[0004] Therefore, based on the existing technology, the present invention creatively uses metal powder as raw material to make a core rod, and then inserts the core rod into a silicon bronze alloy cladding tube to obtain an aluminum silicon copper strip through melting, rolling and other steps, aiming to improve the component accuracy, product surface properties and mechanical properties of the aluminum silicon copper strip. Summary of the invention

[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for preparing an emulsion-type polyacrylamide for treating papermaking wastewater.

[0006] To achieve the above object, the present invention provides the following technical solutions: A method for preparing an aluminum-silicon-copper strip comprises the following steps: S1. According to the mass fraction, 35-50 parts of aluminum-silicon alloy powder, 10-20 parts of aluminum-copper alloy powder and 30-55 parts of aluminum powder are mixed and stirred to obtain a mixed powder; S2. The mixed powder obtained in step S1 is melted, poured into a preheated mold after melting, and kept at 400-450°C for 2-3h, and then placed in an annealing furnace at 340-360°C for annealing and kept for 2-6h to obtain a precursor alloy material; S3. Preparation of modified second phase particle dispersion: mixing the modified second phase particles and the dispersant in a ratio of 1:5-10, and obtaining a modified second phase particle dispersion by ultrasonic dispersion; S4. Preparation of modified precursor alloy material: The precursor alloy material prepared in step S2 is heated to a molten state, and 4-7 parts of the modified second phase particle dispersion are slowly added to the liquid precursor alloy material under stirring conditions, and the addition process lasts for 10-20 minutes. After the addition is completed, stirring is continued for 15-30 minutes to obtain a modified precursor alloy material; S5. The modified precursor alloy material obtained in step S4 is processed into a cylindrical mandrel; S6. Selecting a silicon bronze alloy tube as a cladding tube, and inserting the cylindrical mandrel obtained in step S3 into the silicon bronze alloy tube to form a preform; S7. The preform obtained in step S6 is horizontally moved into a furnace at a heating rate of 15-25K / min, and the temperature is raised to 1000-1200°C. At this time, the preform is in a molten state. Under the assistance of ultrasound, the core rod in the preform and the silicon bronze alloy tube are fully fused while rotating to obtain a strip molten liquid. S8. Extrude, roll, anneal, and then draw and slit the strip molten liquid obtained in step S7 to obtain an aluminum-silicon-copper strip.

[0007] Preferably, in step S2, the smelting temperature is 670-700°C.

[0008] Preferably, in step S3, the preparation of the modified second phase particles comprises the following steps: S301. Alumina and silicon carbide are mixed in a ratio of 2-4:1 to obtain mixed particles; S302. The mixed particles are placed in the reaction chamber of the CVD reactor, evacuated and purged with argon gas to remove air and impurities in the reaction chamber, and then the reaction chamber is heated to 500-800°C; S303. Trimethylaluminum and hydrogen are introduced, the flow rate of trimethylaluminum is 30-60sccm, and the flow rate of hydrogen is 200-500sccm. Trimethylaluminum is decomposed at high temperature, and aluminum atoms are deposited on the surface of the mixed particles to obtain modified second phase particles.

[0009] Preferably, in step S3, the dispersant is one or more of ethanol and acetone.

[0010] Preferably, in step S3, the parameters of ultrasonic dispersion are: 50-150kHz, 100-200W, and time is 1-2h.

[0011] Preferably, in step S4, the stirring speed is 300-500 r / min.

[0012] Preferably, in step S5, the diameter of the cylindrical core rod is 1-2 mm.

[0013] Preferably, in step S6, the thickness of the silicon bronze alloy tube is 0.5-0.8 mm.

[0014] Preferably, in step S7, the parameters of ultrasound assistance are 50-150kHz and 100-200W.

[0015] Preferably, in step S7, the rotation speed is 45-90° / s.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention introduces modified second phase particles into the alloy to modify the precursor alloy material, and makes them evenly distributed in the matrix through a suitable preparation process. These modified second phase particles can hinder dislocation movement, and at the same time improve the strength of the material to a certain extent, and can induce coordinated deformation mechanisms such as Lisheng deformation in the matrix during deformation, thereby improving the plastic deformation ability of the material, thereby improving flexibility and ductility.

[0017] 2. The present invention creatively uses metal and alloy powders as raw materials to precisely control the content of each component. The metal and alloy powders are smelted and annealed to form a cylindrical core rod, which is inserted into a silicon bronze alloy cladding tube. The strip fusion liquid is obtained by melting and ultrasonic assistance, and finally, the strip is post-processed (extrusion, rolling, annealing, drawing and slitting) to obtain an aluminum-silicon-copper strip with certain flexibility, extensibility, strong surface rigidity and good mechanical properties. The aluminum-silicon-copper strip not only has good processing performance, but also has high surface properties of toughness, wear resistance, corrosion resistance and strong tensile strength, is suitable for more severe environments, greatly expands its application range, and has broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The present invention is a schematic diagram of a process for preparing an aluminum-silicon-copper strip. DETAILED DESCRIPTION

[0019] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] See also Figure 1 , the present invention provides a technical solution: Example 1

[0021] A method for preparing aluminum-silicon-copper strip: S1. 35g of aluminum-silicon alloy powder, 10g of aluminum-copper alloy powder and 30g of aluminum powder were mixed and stirred to obtain a mixed powder; S2. The mixed powder obtained in step S1 is melted at 670°C, poured into a preheated mold after melting, and kept at 400°C for 2h, and then placed in an annealing furnace at 340°C for 2h to obtain a precursor alloy material; S3. Preparation of modified second phase particles: S301. Alumina and silicon carbide are mixed in a ratio of 2:1 to obtain mixed particles; S302. The mixed particles are placed in a reaction chamber of a CVD reactor, evacuated, and purged with argon gas to remove air and impurities in the reaction chamber, and then the reaction chamber is heated to 500°C; S303. Trimethylaluminum and hydrogen are introduced, the flow rate of trimethylaluminum is 30 sccm, and the flow rate of hydrogen is 200 sccm. Trimethylaluminum is decomposed at high temperature, and aluminum atoms are deposited on the surface of the mixed particles to obtain modified second phase particles.

[0022] S4. Preparation of modified second phase particle dispersion: The modified second phase particles were mixed with 40% ethanol by mass concentration in a ratio of 1:5, and subjected to ultrasonic dispersion treatment at 50kHz and 100W for 1h to obtain a modified second phase particle dispersion; S5. Preparation of modified precursor alloy material: The precursor alloy material prepared in step S2 is heated to a molten state, and 4 g of the second phase particle dispersion is slowly added to the liquid precursor alloy material under stirring at a stirring speed of 300 r / min. The addition process lasts for 10 min. After the addition is completed, stirring is continued for 15 min to obtain a modified precursor alloy material; S6. The modified precursor alloy material obtained in step S4 is processed into a cylindrical mandrel having a diameter of 1 mm; S7. Selecting a silicon bronze alloy tube with a tube thickness of 0.5 mm as a cladding tube, and inserting the cylindrical mandrel obtained in step S3 into the silicon bronze alloy tube to form a preform; S8. The preform obtained in step S6 is horizontally moved into the furnace at a heating rate of 15 K / min, so that the axis of the preform is parallel to the ground, and the temperature is raised to 1000° C. At this time, the preform is in a molten state. Under the assistance of 50 kHz and 100 W ultrasound, the core rod in the preform and the silicon bronze alloy tube are fully fused to obtain a strip molten liquid; at the same time, the preform is rotated in the furnace at a rotation speed of 45° / s; S9. The strip molten liquid obtained in step S7 is extruded, rolled, annealed, and then drawn and slit (this is the prior art and will not be described again here) to obtain an aluminum-silicon-copper strip with a thickness of 0.35 mm. Example 2

[0023] A method for preparing aluminum-silicon-copper strip: S1. 50g of aluminum-silicon alloy powder, 20g of aluminum-copper alloy powder and 55g of aluminum powder were mixed and stirred to obtain a mixed powder; S2. The mixed powder obtained in step S1 is melted at 700°C, poured into a preheated mold after melting, and kept at 450°C for 3h, then placed in an annealing furnace at 360°C and kept for 6h to obtain a precursor alloy material; S3. Preparation of modified second phase particles: S301. Alumina and silicon carbide are mixed in a ratio of 4:1 to obtain mixed particles; S302. The mixed particles are placed in a reaction chamber of a CVD reactor, evacuated, and purged with argon gas to remove air and impurities in the reaction chamber, and then the reaction chamber is heated to 800°C; S303. Trimethylaluminum and hydrogen are introduced, the flow rate of trimethylaluminum is 60 sccm, and the flow rate of hydrogen is 500 sccm. Trimethylaluminum is decomposed at high temperature, and aluminum atoms are deposited on the surface of the mixed particles to obtain modified second phase particles.

[0024] S4. Preparation of modified second phase particle dispersion: The modified second phase particles were mixed with acetone having a mass concentration of 40% in a ratio of 1:10, and subjected to ultrasonic dispersion treatment at 150kHz and 200W for 2h to obtain a modified second phase particle dispersion; S5. Preparation of modified precursor alloy material: The precursor alloy material prepared in step S2 is heated to a molten state, and 7 g of the second phase particle dispersion is slowly added to the liquid precursor alloy material under stirring conditions at a stirring speed of 500 r / min. The addition process lasts for 20 min. After the addition is completed, stirring is continued for 30 min to obtain a modified precursor alloy material; S6. The modified precursor alloy material obtained in step S4 is processed into a cylindrical mandrel having a diameter of 2 mm; S7. Selecting a silicon bronze alloy tube with a tube thickness of 0.8 mm as a cladding tube, and inserting the cylindrical mandrel obtained in step S3 into the silicon bronze alloy tube to form a preform; S8. The preform obtained in step S6 is horizontally moved into the furnace at a heating rate of 25 K / min, so that the axis of the preform is parallel to the ground, and the temperature is raised to 1200° C. At this time, the preform is in a molten state. Under the assistance of 150 kHz and 200 W ultrasound, the core rod in the preform and the silicon bronze alloy tube are fully fused to obtain a strip molten liquid; at the same time, the preform is rotated in the furnace at a rotation speed of 90° / s; S9. The strip molten liquid obtained in step S7 is extruded, rolled, annealed, and then drawn and slit (this is the prior art and will not be described again here) to obtain a 1.05 mm thick aluminum-silicon-copper strip. Example 3

[0025] A method for preparing aluminum-silicon-copper strip: S1. 40g of aluminum-silicon alloy powder, 15g of aluminum-copper alloy powder and 40g of aluminum powder were mixed and stirred to obtain a mixed powder; S2. The mixed powder obtained in step S1 is melted at 680°C, poured into a preheated mold after melting, and kept at 420°C for 2.5h, then placed in an annealing furnace at 350°C and kept warm for 3h to obtain a precursor alloy material; S3. Preparation of modified second phase particles: S301. Alumina and silicon carbide are mixed in a ratio of 3:1 to obtain mixed particles; S302. The mixed particles are placed in a reaction chamber of a CVD reactor, evacuated, and purged with argon gas to remove air and impurities in the reaction chamber, and then the reaction chamber is heated to 600°C; S303. Trimethylaluminum and hydrogen are introduced, the flow rate of trimethylaluminum is 40 sccm, and the flow rate of hydrogen is 300 sccm. Trimethylaluminum is decomposed at high temperature, and aluminum atoms are deposited on the surface of the mixed particles to obtain modified second phase particles.

[0026] S4. Preparation of modified second phase particle dispersion: The modified second phase particles were mixed with acetone having a mass concentration of 40% in a ratio of 1:6, and ultrasonically dispersed at 80kHz and 130W for 1.5h to obtain a modified second phase particle dispersion; S5. Preparation of modified precursor alloy material: The precursor alloy material prepared in step S2 is heated to a molten state, and 5 g of the second phase particle dispersion is slowly added to the liquid precursor alloy material under stirring at a stirring speed of 400 r / min. The addition process lasts for 15 min. After the addition is completed, stirring is continued for 20 min to obtain a modified precursor alloy material; S6. The modified precursor alloy material obtained in step S4 is processed into a cylindrical mandrel having a diameter of 1.4 mm; S7. Selecting a silicon bronze alloy tube with a tube thickness of 0.6 mm as a cladding tube, and inserting the cylindrical mandrel obtained in step S3 into the silicon bronze alloy tube to form a preform; S8. The preform obtained in step S6 is horizontally moved into the furnace at a heating rate of 20 K / min, so that the axis of the preform is parallel to the ground, and the temperature is raised to 1100° C. At this time, the preform is in a molten state. Under the assistance of 80 kHz and 150 W ultrasound, the core rod in the preform and the silicon bronze alloy tube are fully fused to obtain a strip molten liquid; at the same time, the preform is rotated in the furnace at a rotation speed of 60° / s; S9. The strip molten liquid obtained in step S7 is extruded, rolled, annealed, and then drawn and slit (this is the prior art and will not be described again here) to obtain an aluminum-silicon-copper strip with a thickness of 0.58 mm. Example 4

[0027] A method for preparing aluminum-silicon-copper strip: S1. 45g of aluminum-silicon alloy powder, 18g of aluminum-copper alloy powder and 50g of aluminum powder were mixed and stirred to obtain a mixed powder; S2. The mixed powder obtained in step S1 is melted at 690°C, poured into a preheated mold after melting, and kept at 440°C for 2.7h, and then placed in an annealing furnace at 355°C and kept for 5h to obtain a precursor alloy material; S3. Preparation of modified second phase particles: S301. Alumina and silicon carbide are mixed in a ratio of 3:1 to obtain mixed particles; S302. The mixed particles are placed in the reaction chamber of the CVD reactor, evacuated and purged with argon gas to remove air and impurities in the reaction chamber, and then the reaction chamber is heated to 700°C; S303. Trimethylaluminum and hydrogen are introduced, the flow rate of trimethylaluminum is 50 sccm, and the flow rate of hydrogen is 400 sccm. Trimethylaluminum is decomposed at high temperature, and aluminum atoms are deposited on the surface of the mixed particles to obtain modified second phase particles.

[0028] S4. Preparation of modified second phase particle dispersion: The modified second phase particles were mixed with 40% ethanol by mass concentration in a ratio of 1:8, and ultrasonically dispersed at 140kHz and 180W for 1.8h to obtain a modified second phase particle dispersion; S5. Preparation of modified precursor alloy material: The precursor alloy material prepared in step S2 is heated to a molten state, and 6 g of the second phase particle dispersion is slowly added to the liquid precursor alloy material under stirring at a stirring speed of 450 r / min. The addition process lasts for 18 min. After the addition is completed, stirring is continued for 25 min to obtain a modified precursor alloy material; S6. The modified precursor alloy material obtained in step S4 is processed into a cylindrical mandrel having a diameter of 1.6 mm; S7. Selecting a silicon bronze alloy tube with a tube thickness of 0.7 mm as a cladding tube, and inserting the cylindrical mandrel obtained in step S3 into the silicon bronze alloy tube to form a preform; S8. The preform obtained in step S6 is horizontally moved into the furnace at a heating rate of 23 K / min, so that the axis of the preform is parallel to the ground, and the temperature is raised to 1150° C. At this time, the preform is in a molten state. Under the assistance of 120 kHz and 170 W ultrasound, the core rod in the preform and the silicon bronze alloy tube are fully fused to obtain a strip molten liquid; at the same time, the preform is rotated in the furnace at a rotation speed of 80° / s; S9. The strip molten liquid obtained in step S7 is extruded, rolled, annealed, and then drawn and slit (this is the prior art and will not be described again here) to obtain a 0.87 thick aluminum-silicon-copper strip.

[0029] Comparative Example 1 A method for preparing aluminum-silicon-copper strip: S1. 35g of aluminum-silicon alloy powder, 10g of aluminum-copper alloy powder and 30g of aluminum powder were mixed and stirred to obtain a mixed powder; S2. The mixed powder obtained in step S1 is melted at 670°C, poured into a preheated mold after melting, and kept at 400°C for 2h, and then placed in an annealing furnace at 340°C for 2h to obtain a precursor alloy material; S3. The precursor alloy material obtained in step S2 is processed into a cylindrical mandrel having a diameter of 1 mm; S4. Selecting a silicon bronze alloy tube with a tube thickness of 0.5 mm as a cladding tube, and inserting the cylindrical mandrel obtained in step S3 into the silicon bronze alloy tube to form a preform; S5. The preform obtained in step S6 is horizontally moved into the furnace at a heating rate of 15 K / min, so that the axis of the preform is parallel to the ground, and the temperature is raised to 1000° C. At this time, the preform is in a molten state. Under the assistance of 50 kHz and 100 W ultrasound, the core rod in the preform and the silicon bronze alloy tube are fully fused to obtain a strip molten liquid; at the same time, the preform is rotated in the furnace at a rotation speed of 45° / s; S6. The strip molten liquid obtained in step S7 is extruded, rolled, annealed, and then drawn and slit (this is the prior art and will not be described again here) to obtain an aluminum-silicon-copper strip with a thickness of 0.35 mm.

[0030] Comparative Example 2 This comparative example 2 performs performance tests on conventional copper / aluminum composite strips.

[0031] Performance Test: With reference to standards GB / T 228.1-2010 and GB / T 31541-2015, the aluminum-silicon-copper strips obtained in Examples 1-4 of the present invention, Comparative Example 1, and the copper / aluminum composite strip of Comparative Example 2 were tested for tensile strength, yield strength, elongation, and interface shear strength, respectively. The test results are shown in Table 1 below: ; According to the above data, it can be seen that, compared with Example 1, Comparative Example 1 omits the modification process of the precursor alloy material, that is, the addition of the modified second phase particle dispersion is omitted; Comparative Example 2 is a conventional copper / aluminum composite strip, which is used for better data comparison with the aluminum-silicon-copper strip obtained by the present invention. And from the test results, it can be seen that the tensile strength, yield strength and interface shear strength of the aluminum-silicon-copper strip prepared by the present invention are significantly enhanced. At the same time, it also has good flexibility and elongation, and the elongation reaches 6.7%, and the processability is significantly enhanced. The addition of the modified second phase particle dispersion can further enhance the various properties of the aluminum-silicon-copper strip, so that the aluminum-silicon-copper strip not only has good processing performance, but also has toughness, wear resistance, corrosion resistance and high surface performance with strong tensile strength, which is suitable for harsher environments, greatly expanding its application range and having broad market prospects.

[0032] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an aluminum-silicon-copper strip, characterized in that: The following steps are involved: S1. According to the mass fraction, 35-50 parts of aluminum-silicon alloy powder, 10-20 parts of aluminum-copper alloy powder and 30-55 parts of aluminum powder are mixed and stirred to obtain a mixed powder; S2. The mixed powder obtained in step S1 is melted, poured into a preheated mold after melting, and kept at 400-450°C for 2-3h, and then placed in an annealing furnace at 340-360°C for annealing and kept for 2-6h to obtain a precursor alloy material; S3. Preparation of modified second phase particle dispersion: mixing the modified second phase particles and the dispersant in a ratio of 1:5-10, and obtaining a modified second phase particle dispersion by ultrasonic dispersion; S4. Preparation of modified precursor alloy material: The precursor alloy material prepared in step S2 is heated to a molten state, and 4-7 parts of the modified second phase particle dispersion are slowly added to the liquid precursor alloy material under stirring conditions, and the addition process lasts for 10-20 minutes. After the addition is completed, stirring is continued for 15-30 minutes to obtain a modified precursor alloy material; S5. The modified precursor alloy material obtained in step S4 is processed into a cylindrical mandrel; S6. Selecting a silicon bronze alloy tube as a cladding tube, and inserting the cylindrical mandrel obtained in step S3 into the silicon bronze alloy tube to form a preform; S7. The preform obtained in step S6 is moved into a furnace at a heating rate of 15-25K / min and heated to 1000-1200°C. At this time, the preform is in a molten state. Under the assistance of ultrasound, the core rod in the preform and the silicon bronze alloy tube are fully fused while rotating to obtain a strip molten liquid. S8. Extrude, roll, anneal, and then draw and slit the strip molten liquid obtained in step S7 to obtain an aluminum-silicon-copper strip.

2. The method for preparing an aluminum-silicon-copper strip according to claim 1, characterized in that: In step S2, the smelting temperature is 670-700°C.

3. The method for preparing an aluminum-silicon-copper strip according to claim 1, characterized in that: In step S3, the preparation of the modified second phase particles comprises the following steps: S301. Alumina and silicon carbide are mixed in a ratio of 2-4:1 to obtain mixed particles; S302. The mixed particles are placed in the reaction chamber of the CVD reactor, evacuated and purged with argon gas to remove air and impurities in the reaction chamber, and then the reaction chamber is heated to 500-800°C; S303. Trimethylaluminum and hydrogen are introduced, the flow rate of trimethylaluminum is 30-60sccm, and the flow rate of hydrogen is 200-500sccm. Trimethylaluminum is decomposed at high temperature, and aluminum atoms are deposited on the surface of the mixed particles to obtain modified second phase particles.

4. The method for preparing an aluminum-silicon-copper strip according to claim 1, characterized in that: In step S3, the dispersant is one or more of ethanol and acetone.

5. The method for preparing an aluminum-silicon-copper strip according to claim 1, characterized in that: In step S3, the parameters of ultrasonic dispersion are: 50-150kHz, 100-200W, and time is 1-2h.

6. The method for preparing an aluminum-silicon-copper strip according to claim 1, characterized in that: In step S4, the stirring speed is 300-500 r / min.

7. The method for preparing an aluminum-silicon-copper strip according to claim 1, characterized in that: In step S5, the diameter of the cylindrical core rod is 1-2 mm.

8. The method for preparing an aluminum-silicon-copper strip according to claim 1, characterized in that: In step S6, the thickness of the silicon bronze alloy tube is 0.5-0.8 mm.

9. The method for preparing an aluminum-silicon-copper strip according to claim 1, characterized in that: In step S7, the parameters of ultrasound assistance are 50-150kHz and 100-200W.

10. The method for preparing an aluminum-silicon-copper strip according to claim 1, characterized in that: In step S7, the rotation speed is 45-90° / s.

Citation Information

Patent Citations

  • A method for preparing aluminum-silicon-copper brazing filler metal

    CN103464935B

  • A copper / aluminum composite strip and its preparation method

    CN104669705B